Application of the Nexus Approach as an Integrated Urban Planning Framework: From Theory to Practice and Back Again - Gondhalekar, Daphne; Erlbeck, Ruth (Frontiers in Sustainable Cities, 2021)
Urbanization has created some of the world’s greatest development challenges. At the same time, cities present an opportunity to tackle these challenges comprehensively. For this, an integrated urban development approach is needed. The Water-Energy-Food (WEF) Nexus approach offers cities an integrated urban planning framework to devise sustainability pathways. However, so far there exist no comprehensive guidelines to aid municipal government decision-making on how to apply the Nexus approach in an urban context. This paper highlights the origins of the WEF Nexus approach within the integrated urban planning discourse. It explains the method to introduce Nexus with special emphasis on Nexus training supporting the implementation of the Nexus approach. The “Urban Nexus Development Cycle” as part of the Nexus training, guiding urban practitioners to overcome „silo thinking” is the innovative element as well as the pro-active involvement of universities in the Nexus process.